UTERINE FACTOR INFERTILITY - Valencia Madera, Iván (2015)
The uterus is a dynamic organ. It not only suffers modifications and responds to menstrual cycle hormone signals, but also consists in complex tissues with important anatomic and paracrine functions. The endometrium is its most dynamic component, with characteristic series of cyclic, synchronic and complex phenomena modulated and regulated by several locally produced biochemical agents. The entire dynamic sequence of morphologic and biochemical phenomena contributes to the embryo implantation as well as its nourishing and maintenance during the first development stages.